2022
DOI: 10.24959/nphj.22.77
|View full text |Cite
|
Sign up to set email alerts
|

Development the composition and technology for obtaining a dietary supplement “Cachinol” with the antioxidant activity in the form of granules used in the polycystic ovary syndrome

Abstract: Aim. To develop the composition and technology for obtaining a dietary supplement “Cachinol” with the antioxidant activity in the form of granules used in the polycystic ovary syndrome. Materials and methods. To achieve the goal, physical, physicochemical, pharmacotechnological and statistical research methods, as well as generally accepted research methods of the State Pharmacopoeia of Ukraine (SPhU) 2.0 were used in the work. Results and discussion. The rational dosage form is granules. The green tea leaf ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Oxidative stress is a condition characterized by an excessive presence of reactive oxygen species, such as superoxide, hydroxyl radical, hypochlorite, and singlet oxygen. These reactive oxygen species can lead to cellular damage through oxidative stress [31]. Among the enzymes responsible for generating reactive oxygen species is NADPH oxidase, which stands out as the sole enzyme devoted exclusively to this function [32].…”
Section: Evaluation Of Anti-inflammatory…mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a condition characterized by an excessive presence of reactive oxygen species, such as superoxide, hydroxyl radical, hypochlorite, and singlet oxygen. These reactive oxygen species can lead to cellular damage through oxidative stress [31]. Among the enzymes responsible for generating reactive oxygen species is NADPH oxidase, which stands out as the sole enzyme devoted exclusively to this function [32].…”
Section: Evaluation Of Anti-inflammatory…mentioning
confidence: 99%
“…In many chronic diseases such as diabetes mellitus, hypertension, atherosclerosis, Alzheimer's disease, and cancer [1], inflammation and oxidative stress invariably play pivotal roles. During the inflammatory response, neutrophils and macrophages generate substantial quantities of free radicals to combat and eliminate foreign invaders [2,3]. Furthermore, recent research has revealed that non-phagocytic cells, like interleukin-6 (IL-6), can also produce free radicals by expressing NADPH oxidase [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to endogenous or exogenous influences, the antioxidant system is not always able to completely inactivate free radicals, thereby increasing the risk of developing the diseases above. Therefore, natural antioxidants found in food are consumed, and in addition, special foods and medicines are added to the daily diet to support the antioxidant system [7,8].…”
mentioning
confidence: 99%
“…Аналіз останніх досліджень і публікацій. Розроблення гранул на основі лікарської рослинної сировини висвітлено в роботах багатьох учених [1,2,[5][6][7][8]. За результатами аналізу наукових першоджерел з'ясовано, що асортимент гранул на фармацевтичному ринку України є незначним.…”
unclassified
“…Ефективність лікарського засобу залежить не тільки від природи і дози лікарської речовини, але і від технологічних стадій його виробництва [5][6][7].…”
unclassified